Gravity and Remote Sensing Methods as a Solution in Identifying Geothermal Reservoirs on Volcanoes - null Wiyono; Salman Hamja Siombone; Sukir Maryanto (International Journal of Geophysics)
Tiris Village, Lamongan Volcano complex is an area that has geothermal potential. The existence of geothermal potential in this study was identified using the gravity method combined with remote sensing methods. Remote sensing method is used to obtain a map of the distribution pattern of the soil surface temperature and a map of the continuity of the straightness and fault structure. The data used in the remote sensing method is secondary data in the form of Landsat-8 imagery and DEM SRTM 1 arc. Processing of the soil surface temperature map was obtained by using thermal infrared processing NDVI. The form of continuity of the straightness or fault structure is obtained by processing Landsat-8 multispectral image data in the form of 567 band composite and DEM SRTM data form of 3D topographic modeling. The data from the composite band 567 was reviewed visually using a 3D topographic model. The gravity method is the main method in this research because it is used to obtain the residual Bouguer anomaly distribution. The residual Bouguer anomaly data was obtained by using the moving average through spectrum analysis. The residual Bouguer anomaly distribution can be used for qualitative interpretation of the distribution of the earth’s gravitational acceleration at the measurement location. The quantitative interpretation of the gravity data is based on the surface density estimation graph using the Parasnis method and 3D inversion modeling, using residual Bouguer anomaly data. The results of 3D inversion modeling provide four types of subsurface rock layers based on the density distribution value, namely, the first rock layer ρ1=2.52–2.67 g/cm3, the second rock layer ρ2=2.72–2.77 g/cm3, the third rock layer ρ3=2.80–2.83 g/cm3, and the fourth rock layer ρ4=2.84–2.86 g/cm3. The third rock layer is assumed to be reservoir rock and is estimated to be at a depth of 500–800 meters below the measurement point. The fourth rock layer is assumed to be intrusive igneous rock, which penetrates dominantly in the middle of the measurement location, which is oriented southwest, south to north, which is indicated by the high anomaly continuity on the regional Bouguer anomaly map. Based on the results of 3D inversion modeling and spectrum analysis of the average depth of the regional Bouguer anomaly, it is found that the intrusive rock layer is thought to be at a depth of 350 meters below the measurement point.